Thematic and Stylistic Analysis of Sparks’ The Last Song: In-Depth Exploration of Literary Writing: In-depth exploration on writing fluency - Simanjuntak, Debora (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
This study aimed to reveal the elements of Sparks’ writing style and his chosen themes for an in-depth exploration of literary writing. The data for this study was textual, coming from Sparks’ The Last Song. It was conducted within the framework of two theories: Aestheticism and Stylistics. It was found that Sparks utilizes binary opposite themes, which are: Hatred Vs Love, Death Vs Life, Adultery Vs Fidelity, Distrust Vs Faith, Alienation Vs Closeness, Poverty Vs Wealth, and Illusion Vs Reality. These themes become completely effective as they are supported by his style of narrating the story. Sparks’ style is analyzed in terms of the following elements: Figurative languages of speech, Syntax/Sentence Fluency, Diction/Choice of Words, Point of View, Types of discourses, and Plot Devices. Through the analysis of Sparks’ novel, implications for literary appreciation and creative writing were drawn. The implications for literary appreciation are: read to enjoy the literature, enhance the enjoyment of literature, and develop a passion for literature. The implications for creative writing are: practice creative reading, think critically and analytically, write pictorially and aurally, and fictionalize a true-to-life story.